PERBAIKAN KUALITAS BIJI KEDELAI TERKONTAMINASI LOGAM BERAT DANFORMASI KOMPLEK PHYTOCHELATIN - Setie Harieni; Sapto Priyadi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
A study on the improvement of the quality of soybean seeds contaminated heavy metal and formation complex of phytochelatin. This research was the improvement of the quality of soybean seed stage through chelation. Research factors include: citric acid chelating agent (C) consists of three levels (1, 2 and 3 g); contact time of chelation (D) consists of three levels (90, 120 and 180 minutes) and the seeds condition (E), consists of three levels (whole, ruptured and flour). The results showed that the highest Pb reduction achieved in the treatment of C1D1E1 [chelation used chelating agent (1 g), contact time 90 minutes and whole bean conditions] werechelation conditioned at pH 10. On the basis of highest reductionand provisional tolerable daily intake, thus should be consumed human beings 80,1826 g soybeans kg–1 body weight day–1 (increased 5.39 times from pre-chelation). The data reduction of the highest achieved in the Cd all chelation treatment a conditioned at pH 10, thus should be consumed human beings 1.127,8195 g soybeans kg–1 body weight day–1(increased 10,53 times from pre-chelation). Phytochelatin complex at neutral pH, coordinated by COO– from cysteine ligands, whereas at pH 11 were on the formation of mononuclear coordination of cadmium (II)cysteine [Cd(S,N–Cys)2]2– (CdS2N2),coordinated by cysS– from cysteine ligands. Heavy metals Pb and Cd contained in the complex Cd and Pb phytochelatin of exposed cells.